Inequality Persistence in Papua and West Papua through Urban Rural Spatial Divergence - Kevin Jonathan Wijaya; Yohanes Michael Kogoya; Samuel Tabuni; Maria Kogoya; Grace Wambrauw (Journal of Economics Business Industry, 2026)
This study analyzes the persistence of consumption inequality in Papua and West Papua by emphasizing the role of spatial divergence between urban and rural areas. The study uses six waves of Indonesia’s National Socioeconomic Survey (SUSENAS) from March 2010, 2014, 2017, 2020, 2022, and 2025, with a consistent classification of ten spatial zones to ensure comparability before and after administrative expansion. The methods employed include Shapley decomposition to separate spatial and non-spatial inequality across the Gini index, Mean Log Deviation, Theil index, and GE(2), as well as Recentred Influence Function (RIF) regression and the Blinder-Oaxaca approach to identify regional contributions and household-level determinants. The findings show that consumption inequality increased from a Gini coefficient of 0.355 in 2010 to 0.412 in 2020, declined to 0.389 in 2022, and rose again to 0.393 in 2025. Since 2014, spatial inequality has become the main driver of rising inequality, particularly through the concentration of formal economic activity and mining rents in Jayapura and Timika, alongside the continued isolation of rural areas in the Papuan Highlands. Education and participation in non-subsistence employment are identified as key mediating factors that reinforce disparities across spatial zones. These findings indicate that reducing inequality in Papua and West Papua requires policies that go beyond fiscal transfers, including equal access to education, market integration, infrastructure development, and conflict resolution in highland areas.